Herbs, Home Medicine, and Self-Reliance: A Study on the Current Status of Traditional Home Medicine in Idukki District, Kerala - Richard Gaunt (Independent Study Project (ISP) Collection. Paper 2078, 2015)
Home medical knowledge, or knowledge of how one’s surroundings can be used to maintain and restore health, can be an important tool for health self-sufficiency in rural places as well as for the ecological conservation of important plants and natural materials. The Indian state of Kerala has a rich heritage of traditional medicine, found in the historically inter-related forms of codified Ayurveda and folk knowledge. In Idukki district, a region of Kerala nestled in the hills of the Western Ghats, rural households engage in small-scale home-gardening and agroforestry, which in addition to providing nutritionally diverse food is a source of medicinal herbs and home remedies. This study interviewed 35 households in the village of Mankulam, Idukki District regarding their knowledge and utilization of herbs and home-remedies. A total of 80 local plants and substances were identified as being used by villagers for medicinal purposes, to cure or prevent wide varieties of ailments. Families with extensive use and knowledge of home medicine also engaged in intensive home gardening practices which integrated their food and medicine cultivation. While a basic knowledge and use of at least a few medicinal plants in the home is nearly ubiquitous, more extensive knowledge of advanced remedies and plants is still present but quickly disappearing. Though a majority of families responded that they find natural remedies to be superior to Allopathic ones, many of these are increasingly relying on Allopathic medicines. Factors found to be contributing to this paradox include changing lifestyles, the convenience factor of Allopathy, and diminishing home-cultivation of medicinal plants.